PROSES PEMBUATAN SERTA ANALISA BENTON-38 DARI BENTONIT SEBAGAI BAHAN ADITIF PADA CAT - Tasrif Tasrif; Nuryatini Nuryatini; Siti Isnijah (Research Center for Chemistry - LIPI, 1995)
The production of bentone for paint additive from Cabentonite was carried out by ion exchange process. The process has two steps, i.e. Ca++ ion in Ca-bentonite is exchanged by Na+ ion in saturated solution of NaCl to produce Na-bentonite. Then, Na+ ion in Na-bentonite is exchanged into (R1)2N(R2)2 + by using alkyl quaternary ammonium salt to produce bentone. lnterms of swelling characteristic the ion exchange using 140 ml of saturated solution of NaCl for 100 g Ca-bentonite produced best product with a swelling characteristic of 15.56. The amount of dimethyl distearyl ammonium salt (DAM) used for production of bentone-38 was 60 g/100 g bentonite. This is based on the ion exchange capacity of bentone-38, i.e. 69 meq for 100 g bentonite. Swelling characteristics of the above bentone-TS-R (reference) and bentone-38-H (experiment) were 24.5 and 39 in Spirit Mineral Terplne (SMT), 55 and 54 in SMT + ethanol (17:3 v/v), and the viscosity of bentone-38-R, and bentone-38-H are 7.2 cps and 6.5 cps respectively.",